2009
DOI: 10.1159/000226219
|View full text |Cite
|
Sign up to set email alerts
|

How to Prevent Lateral Thermal Damage to Tissue Using the Harmonic Scalpel: Experimental Study on Pig Small Intestine and Abdominal Wall

Abstract: Introduction: When using a harmonic scalpel, the lower amount of energy that is transduced to the tissue reduces the chance of lateral thermal damage. Methods: Pigs (weight: 40 kg) were used as the experimental model. After anesthesia, tissue was coagulated using different application regimens for each group. The width of tissue necrosis was measured from the point of incision by the harmonic scalpel. Results: The pig abdominal tissues suffered mean thermal damage of 0.0825 (output power 3) and 0.2969 mm (outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The short duration of peritoneal contact with a hook probably explains the more favorable outcome in our study than in the study of Kim et al [4]. Lateral thermal injury also was less in pig intestine and abdominal wall when energy was applied with pauses in contrast to the continuous activation of the Harmonic Scalpel [29]. …”
Section: Discussionmentioning
confidence: 40%
“…The short duration of peritoneal contact with a hook probably explains the more favorable outcome in our study than in the study of Kim et al [4]. Lateral thermal injury also was less in pig intestine and abdominal wall when energy was applied with pauses in contrast to the continuous activation of the Harmonic Scalpel [29]. …”
Section: Discussionmentioning
confidence: 40%
“…In addition, European Surgical Research (2009) reported that coagulation necrosis is greater if the utilization is nonstop rather than separated or reconnected. Studies on porcine and rodent abdominal walls showed that the lateral thermal tissue damage is directly related to duration of application, being greater when a long continuous period is utilized irrespectively if the USADs are used in the standard output power and likewise when the USADs’ application is not followed by a short pause between applications 18. Moreover, the performance of currently laparoscopic USAID’s is different in terms of vessel sealing speed (mean time), vessel burst pressure (mmHg), visibility, operation time and degree of thermal damage (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The blade vibrates at 55.5 kHz; in this way, it generates less heat from tissue friction. Laser and electrosurgical energies create a temperature range between 100 and 400°C, at which tissue dehydration (100-150°C) and charring (>150°C) occur [19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic energy delivered by means of an HS has been shown to be safe and to produce minimal damage to the surrounding tissues, especially with an application time less than 5 s [19,20]. Minimal heat production with the HS leads to a minimal zone of thermal injury and better healing compared with electrosurgery and lasers [9].…”
Section: Discussionmentioning
confidence: 99%